2009
DOI: 10.4161/cbt.8.1.7090
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide mRNA profiling of esophageal squamous cell carcinoma for identification of cancer biomarkers

Abstract: Cancer of the esophagus is of two main types, each with distinct etiological and pathological characteristics. Esophageal squamous cell carcinoma (ESCC) is predominant type of esophageal cancers worldwide comprising almost 95% of cases. While ESCC is prevalent in the developing world, esophageal adenocarcinoma is commonly seen in the developed country, usually in association with Barrett's esophagus. In spite of its higher prevalence, ESCC has not been studied as intensively as esophageal adenocarcinoma. ESCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 66 publications
(64 reference statements)
4
87
0
1
Order By: Relevance
“…mRNA profiling of ESCC tissues demonstrated an upregulation of periostin as high as 11-fold (13). Similarly, a quantitative tissue proteomic study reported a 7-fold upregulation of periostin in tumor tissues compared with normal tissues (14). However, a further study investigated whether periostin was secreted by cancer cells or non-epithelial cells, including cancer-associated fibroblasts, and it was observed that it was primarily produced by the latter.…”
Section: Periostin In Esophageal Cancermentioning
confidence: 99%
“…mRNA profiling of ESCC tissues demonstrated an upregulation of periostin as high as 11-fold (13). Similarly, a quantitative tissue proteomic study reported a 7-fold upregulation of periostin in tumor tissues compared with normal tissues (14). However, a further study investigated whether periostin was secreted by cancer cells or non-epithelial cells, including cancer-associated fibroblasts, and it was observed that it was primarily produced by the latter.…”
Section: Periostin In Esophageal Cancermentioning
confidence: 99%
“…The 11q13 amplicon is one of the most frequently amplified chromosomal regions in human cancer and correlates with a poor prognosis (3)(4)(5)(6)(7). Although cyclin D1 (CCND1) has been considered to be the main driver of the 11q13 amplicon (8)(9)(10), it is not sufficient for malignant transformation of normal breast cells and lacks predictive value for the survival of head-and-neck squamous cell carcinoma (HNSCC) or breast cancer patients (8,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…For example, genetic mutations in TMEM16C, -16E, -16F, and -16K are associated with craniocervical dystonia (14), musculoskeletal disorder (15,16), bleeding disorder (9), and cerebellar ataxia (17), respectively. TMEM16A is overexpressed in human gastrointestinal stromal tumors and in head and neck squamous carcinoma; TMEM16G is overexpressed in prostate cancer (18,19). Thus, compounds that modulate the function of TMEM16A have been explored for the treatment of human diseases such as cystic fibrosis, hypertension, secretory diarrheas, asthma, and cancer (20).…”
mentioning
confidence: 99%